Respuesta :

DWRead

Answer:

Step-by-step explanation:

y = -x-3

y = x^2 + 4x + 1

x^2 + 4x + 1 = -x-3

x^2 + 5x + 4 = 0

Quadratic Formula

x = [-5±√(5²-4⋅1⋅4)]/[2⋅1] = [-5±√9]/2 = [-5±3]/2 = 1,-4

(x,y) = (1,-4) of(-4,1)

Answer:

x = -4,  y = 1

x = -1,   y = -2

Step-by-step explanation:

(1)     x + y = -3                  (2)    y = [tex]x^{2} +4x + 1[/tex]

             y = -x - 3                   -x - 3 =  [tex]x^{2} +4x + 1[/tex]

                                                     [tex]x^{2} + 5x + 4 = 0\\[/tex]

                                                    (x + 4)(x + 1) = 0

                                                         x = -4  or x = -1

            y = -(-4) - 3 = 4 - 3 = 1

            y = -(-1) - 3 = 1 - 3 = -2

ACCESS MORE